The damage evolution law and life prediction of mortar under Freeze-thaw cycles and sulfate corrosion based on entropy weight method - Yizheng Jiang; Yuang Cui; Yi Song; Xuepeng Zhang (Case Studies in Construction Materials)
Freeze-thaw cycles coupled with sulfate attack represent one of the most challenging service environments for concrete. This study aims to enhance the durability of concrete materials in environments characterized by sulfate attack and severe freeze-thaw conditions. Specifically, it investigates the deterioration laws and evolution models of mortar materials containing silica fume under both freeze-thaw and coupled freeze-thaw/sulfate attack conditions. Mortar specimens with varying silica fume contents (0 %, 6 %, 8 %, and 10 %) were prepared and subjected to single freeze-thaw and coupled freeze-thaw-sulfate attack tests to examine the impact of different silica fume dosages on the durability of mortar materials under these harsh conditions. Additionally, a quantitative assessment model for damage evolution was established using the entropy weight method and Wiener process model. The research findings indicate that silica fume significantly enhances the sulfate resistance and freeze-thaw durability of mortar materials, with an optimal dosage of 10 %. Within the scope of this study, higher silica fume content results in a greater number of sulfate attack-freeze-thaw cycles the mortar can endure before damage and failure, thereby extending its service life. Based on the Wiener stochastic process damage model and field data, it is predicted that the service life of mortar containing 10 % silica fume increases most notably to 36.6 years, representing a relative improvement of 45.8 % compared to mortar without silica fume. These results provide valuable references and guidance for the design and construction of concrete structures in regions characterized by high-cold temperatures and salt-corrosive soils.